Clobazam‐treated patients with Lennox‐Gastaut syndrome experienced fewer seizure‐related injuries than placebo patients during trial OV‐1012. (4th May 2016) - Isojarvi, Jouko; Lee, Deborah; Peng, Guangbin; Sperling, Michael R.
Summary: Drop seizures are especially problematic in patients with Lennox‐Gastaut syndrome (LGS) because of their potential for serious injury. In this post hoc analysis of phase 3 OV‐1012 data, a medical review was conducted of seizure‐related injuries based on Medical Dictionary for Regulatory Activities (MedDRA) preferred terms from all adverse event (AE) listings. Patients receiving clobazam experienced fewer seizure‐related injuries than those receiving placebo (8.9% all clobazam dosages vs. 27.1% placebo, p ≤ 0.05). Significant differences in the rates of seizure‐related injuries were observed for the medium‐ and high‐dosage clobazam treatment groups (4.8% and 10.2%, respectively, p ≤ 0.05). A total of 50 of 53 AEs considered seizure‐related were mild or moderate in intensity; 3 severe AEs occurred in the placebo group (fall, contusion, and jaw fracture). A single serious AE (jaw fracture, which required hospitalization and surgery) occurred in a placebo‐treated patient. Most injuries resolved by the end of the study. This analysis indicates that the reduction in drop‐seizure frequency achieved with clobazam provides a clinically meaningful benefit, a reduced likelihood of experiencing seizure‐related injuries.